Crisis Decision Bundling (CDB) as a crisis leadership framework for digital platform organizations: Integrating dynamic capabilities and situational crisis communication theory in the Netflix Case - Dicky Chandra; Eeng Ahman; Askolani Askolani; Nuryadi Wijiharjono; Indi Ramadhani (Ann Publisher, 2026)
Background. This study examines Netflix’s crisis leadership by integrating crisis leadership theory, dynamic capabilities, and Situational Crisis Communication Theory (SCCT) across four major crises (2000, 2011, 2020, 2022). Methods. A qualitative single-case critical review design is employed. Data include SEC filings, shareholder letters, earnings calls, Investor Relations materials, and relevant international business journalism. Result. Analysis combines heuristic tracing of crisis trajectories with directed qualitative content analysis (Schreier’s coding frame) to reconstruct 14 crisis decisions and assess propositions P1–P4. Findings indicate: the 2000 financial crisis triggered a subscription pivot and a “simplicity–accessibility” identity anchor that aligned early responses under time pressure (P1); the 2011 Qwikster backlash was contained through rapid rollback, public apology, and reunified customer experience, restoring the service’s value frame (P2); the 2020 pandemic disruption was addressed via global–local resource orchestration, release rescheduling, and remote post-production/localization to sustain content supply continuity (P3); and the 2022 subscriber decline prompted monetization reset (AVOD, paid sharing), phased market roll-out, and a shift in performance metrics legitimized through fairness–access–transparency framing (P4). Conclusion. The study’s main contribution is the CDB framework, conceptualizing high-velocity, centrally orchestrated crisis decision bundles that coordinate cross-domain actions and legitimacy framing, turning crises into catalysts of digital platform business-model transformation.